Analisis kebutuhan bahan ajar bahasa Arab bagi calon Tenaga Kerja Indonesia (TKI) di Timur Tengah - Nuruddin, Nuruddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
This study is to describe the needs to develop Arabic language teaching materials for prospective Indonesian migrant workers in Middle East. It is a research and development study adapted from Borg and Gall with the following procedures: reviewing relevant literature, conducting a field observation, studying some collected documentation, and in-depths interviews. The results of the study show that (1) the teaching materials are geared to help the prospective Indonesian migrant workers to communicate, to make their tasks at ease, to understand the culture and customs and relevant documents on employment; (2) the teaching materials are designed as multimedia products; and (3) the teaching materials are developed based on cultural themes and approach.